Real-time 3D sound system with head-tracking - Yang, Runtong (2016)
Established for more than one century, the communication system continues to evolve toward simulating immersive environments that emulate reality. In particular, the concepts of augmented reality (AR) and virtual reality (VR) have recently became increasingly popular with large corporations, such as Oculus, Samsung and Sony launching groundbreaking VR devices. These technological gadgets nevertheless, have focuses their selling points on visual aspect unequally, and valued acoustic experience at a less important role. To explore the possibility of integrating acoustic components with the existing visual technology to achieve a more immersive VR simulation, the objective of this project is aimed at building a portable real-time 3D audio system that takes in monophonic sound source and output with 3D effects, with commercially affordable electronic components. Established on Teensy platform with 3-Space Sensor as head tracker after feasibility analysis on Matlab, this project successfully accomplished the goal by implementing HRTF filtering, and continued to seek to extend the level of functionality by adding equalizers, increasing capacity of sound source intake, and rudimentary simulation on reverberation based on delay algorithm. While this project shows the opportunity of manufacturing affordable 3D audio devices which could potentially supplement the existing VR technology, the output itself could be enhanced in terms of emulating a more real and immersive acoustic experience through techniques that improves sound externalization. Hopefully, the trial on this project would contribute to the integration of audio and visual technology to advance the existing technology towards the innovation of more comprehensive VR devices.